The Challenge of Researching Trust in Intercultural Cooperation - Schwegler, Ulrike (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2009)
A critical element to the successful globalization of business requires the ability to cooperate across cultural borders. Thus, people of different cultural backgrounds are increasingly faced with the challenge of managing unfamiliar situations with unfamiliar people. Exactly this situation is where the ability to establish trusting relationships becomes a critical factor. Despite of the importance of the topic, little research exists on developing trust in intercultural settings. This article analyses the specific conditions of researching trusting relationships across cultures. Etic and emic research designs will be compared and discussed with respect to the specific conditions in cross-cultural and intercultural situations. A discussion is directed at to which extent different research approaches support our understanding of trust as a dynamic concept. The analyses will be used to identify implications relevant for further empirical research. URN: urn:nbn:de:0114-fqs0901486